Graft Utilization in the Augmentation of Large-to-Massive Rotator Cuff Repairs: A Systematic Review. (November 2016) - Ferguson, Devin P.; Lewington, Matthew R.; Smith, T. Duncan; Wong, Ivan H.
Background: Current treatment options for symptomatic large-to-massive rotator cuff tears can reduce pain, but failure rates remain high. Surgeons have incorporated synthetic and biologic grafts to augment these repairs, with promising results. Multiple reviews exist that summarize these products; however, no systematic review has investigated the grafts' ability to maintain structural integrity after augmentation of large-to-massive rotator cuff repairs. Purpose: To systematically review and evaluate the effectiveness of grafts in the augmentation of large-to-massive rotator cuff repairs. Study Design: Systematic review. Methods: A comprehensive search of 4 reputable databases was completed. Inclusion criteria were (1) large-to-massive rotator cuff tear, (2) graft augmentation of primary repairs ± primary repair control group, and (3) minimum clinical and radiologic follow-up of 12 months. Two reviewers screened the titles, abstracts, and full articles and extracted the data from eligible studies. Results were summarized into evidence tables stratified by graft origin and level of evidence. Results: Ten studies fit the inclusion criteria. Allograft augmentation was functionally and structurally superior to primary repair controls, with intact repairs in 85% versus 40% of patients ( P < .01). This was supported by observational study data. Xenograft augmentation failed to demonstrate superiority to primary repair controls, with worse structural healing rates (27% vs 60%; P =.11). Both comparative studies supported this finding. There have also been many reports of inflammatory reactions with xenograft use. Polypropylene patches are associated with improved structural (83% vs 59% and 49%; P < .01) and functional outcomes when compared with controls and xenograft augmentation; however, randomized data are lacking. Conclusion: Augmentation of large-to-massive rotator cuff repairs with human dermal allografts is associated with superior functional and structural outcome when compared with conventional primary repair. Xenograft augmentation failed to demonstrate a statistically significant difference and may be associated with worse rerupture rates and occasional severe inflammatory reactions. Polypropylene patches have initial promising results. Research in this field is limited; future researchers should continue to develop prospective, randomized controlled trials to establish clear recommendations.